THE FLIPPED CLASSROOM TRAINING AS LEARNING MODEL IN NEW NORMAL ERA FOR SCIENTIFIC TEACHERS IN KATINGAN REGENCY - Ruli Meiliawati; AT Siahaan; Anggi Ristiyana Puspita Sari (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
This community service aims to introduce and train the scientific teachers using learning method of blended-learning model flipped classroom as a learning model during new era normal. This program is implemented in SMAN 1 Katingan Hilir. Our model is suitably socialized since combining between asynchronous and synchronous in its learning activity. This community service method is arranged in 3 steps such as: (1) Preparation is consisting of requirement analysis, journal, then doing the observation in target area; (2) Implementation is likely conveying the learning matters, FGD, and RPP product development, and (3) Evaluation is discussion and analysis effort to developed RPP product. As the results of our achievements are (1) teachers and students comprehend regarding blended-learning model, (2) Teachers is capable to develop RPP and analyze to contextual RPP product based on flipped classroom. In addition, the output of this program is a RPP in which it is able to be implemented in daily class room.